Women Entrepreneurs of Rajasthan: Decoding Managerial Skills - Singhal, Dr. Ritesh Kumar; Sudha, Dr. R.; Krishna, Dr. Somanchi Hari; Chordiya, Dr. Kavita; Sinha, Dr. Amit; Acharya, Dr. Namrata (The journal of contemporary issues in business and government, 2022)
Employment has been an obvious marvel in the development of new women entrepreneurs. Men or women are equally endowed with psychological and physical abilities along with managerial abilities that are essential for being a successful entrepreneur. Women are certainly not inferior as many of them are ready to undertake the various type of work if opportunities are provided (Singh N. P., 1985). Nearly a decade back, the International Labour Organization (ILO) 1998 World Employment Report characterized the informal sector in the following words: "Informal units comprise small enterprises with hired workers, household enterprises using mostly family labour, and the self- employed. Women entrepreneurship development can be identified by the motivation amongst women, knowledge and awareness, skill enhancement and training, Decision making and Risk-taking abilities. The objective of the paper is to identify the major challenges and cultural and economic barriers faced by women entrepreneurs in Rajasthan that creates a hindrance in the growth and development of Women entrepreneurship.